ANALYSIS OF CUSTOMER LOYALTY IN SERVICE QUALITY (Study on Customers of Food Court La-Tansa Gontor Ponorogo) - Dizky Novandi Somantri Putra; Mohammad Zaenal Abidin (Islamic Business and Management Journal, 2018)
ABSTRACTThe rapid changes in the current environment are competing to steal and affect the hearts of customers this certainly not separated from the entrepreneur in his business that has its own characteristics in each strategy. Food Court La-Tansa Gontor Ponorogo is one of the culinary business unit owned by Pondok Modern Darussalam Gontor with its unique of service characteristic.The purpose of this study is to examine and analyze the extent to which the services quality implemented in this business unit affect the increase in customer loyalty. The measurement of the quality dimension uses five dimensions of service quality consisting of tangible, reliability, responsiveness, assurance, and empathy dimensions. The research instrument used is questionnaire distributed to 90 customer of Food Court La-Tansa Gontor Ponorogo taken using Non-Probability Sampling technique with Incidental Sampling approach. Data was analyzed by using multiple linear regression analysis to see the service quality dimension that is the most dominant influence on customer loyalty. Based on the results of research that has been done, it showed the five variables of service quality simultaneously affect the customer loyalty and partially tangible and empathy variables that significantly affect customer loyalty. While reliability, responsiveness and assurance no significant influence on customer loyalty.